2009
DOI: 10.1590/s0004-282x2009000400010
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial and spinal ependymoma: series at Faculdade de Medicina, Universidade de São Paulo

Abstract: -Objective: Ependymomas are rare intracranial neuroepithelial tumors and the most common location is intramedullary. The aim was to analyze the characteristics of these tumors to determine the patients' overall survival and the likelihood of recurrence. Method: Data of clinical presentation, tumor location, duration of symptoms, degree of resection and complementary treatment of 34 patients with intracranial ependymoma and 31 with intramedullary ependymoma who underwent surgery in the last ten years were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
0
11
0
1
Order By: Relevance
“…Our research group has previously reported, in parallel, on the prognostic significance of tumor location in adult spinal ependymomas using the same methodology and aggregated data [38]. However, the prognostic significance of tumor location, particularly in intracranial ependymomas, has been debated [39]. We found in the present study that the tumor location of intracranial ependymomas has significant prognostic consequences, as infratentorial location is a more favorable location than supratentorial with respect to PFS and OS in adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research group has previously reported, in parallel, on the prognostic significance of tumor location in adult spinal ependymomas using the same methodology and aggregated data [38]. However, the prognostic significance of tumor location, particularly in intracranial ependymomas, has been debated [39]. We found in the present study that the tumor location of intracranial ependymomas has significant prognostic consequences, as infratentorial location is a more favorable location than supratentorial with respect to PFS and OS in adults.…”
Section: Discussionmentioning
confidence: 99%
“…The opposite pattern, with supratentorial location conferring a more favorable prognosis, has been demonstrated for pediatric intracranial ependymomas [49]. Previous studies have reported conflicting findings as to the attainability of GTR for supratentorial versus infratentorial location [39, 50, 51], two of which suggested that supratentorial ependymomas may possess a more disseminative phenotype that precludes GTR from involved brain parenchyma. In children, supratentorial ependymomas have a higher mitotic activity than infratentorial types [52].…”
Section: Discussionmentioning
confidence: 99%
“…Despite numerous studies done on spinal ependymomas, most studies are limited to experiences gathered from a single institution or a few institutions. 7,34,39,50,57 The goal of this study was to perform a comprehensive literature review with an integrative analysis (where the previously reported individual cas- es are pooled and analyzed) of spinal ependymoma in adult patients who underwent resection to better understand how spinal ependymomas behave differently along the spinal axis. This study is the largest integrative analysis of surgical outcomes in adult spinal ependymoma patients to date.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies indicate that intracranial ependymomas behave differently from spinal ependymomas, 7,8,35,58,59,63 an extensive analysis of ependymoma behavior within the spinal cord has not been conducted. Understanding tumor behavior at different locations along the spinal cord with respect to PFS and OS, for example, could allow more accurate prognosis, tailored management, and better patient counseling.…”
mentioning
confidence: 99%
“…A duração dos sintomas até o diagnóstico pode variar de 1 mês a 3 anos, sendo, geralmente, de 3 a 6 meses nos tumores intracranianos e cerca de 3 anos nas lesões intramedulares (Schwartz and McCormick 2000;Reni, Gatta et al 2007;Andrade, de Aguiar et al 2009). …”
Section: Quadro Clínicounclassified